HHO Gas Productivity Analysis Using A Dry Cell Type HHO Generator With Variations of Copper and Stainless Steel Electrodes, Electric Current, and NaOH Concentration - sugeng hadi susilo; Fica Aida Nadhifatul Aini; Hangga Wicaksono (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
properties and rapid combustion. However, optimizing the performance of dry cell HHO generators remains a significant challenge. This study investigates the effect of varying electrode materials (copper and stainless steel), electric current, and NaOH concentration on HHO gas production. The key performance indicator used is the flow rate of HHO gas produced. Results show that increasing electric current significantly enhances HHO production, though this relationship is non-linear due to the rise in electrolyte temperature and internal resistance. A higher NaOH concentration increases electrolyte conductivity, improving HHO production, but excessive concentrations can lead to higher temperatures and electrode degradation. Copper electrodes outperformed stainless steel in gas production due to better electrical conductivity, while stainless steel exhibited superior corrosion resistance over time. Optimizing the combination of electrode material, current, and NaOH concentration is crucial for enhancing the performance of dry cell HHO generators, offering valuable insights for hydrogen-based energy systems.